ҚУЁШ ҲАВО КОЛЛЕКТОРЛАРИДА ТУРБУЛИЗАТОРЛАР ҚЎЛЛАНИЛГАНИДА ҲАВО ҲАРОРАТИ РЕЖИМИНИ КОМПЬЮТЕРЛИ МОДЕЛЛАШТИРИШ - Узоқов, Ғулом; Ибрагимов, Умиджон; Алиярова, Лола; Хамраев, Сардор (Innovatsion texnologiyalar, 2022)
This article proposes the installation of baffle-turbulator type intensifiers in flat solar air collectors. Theoretically investigated the temperature regime in the solar air collector when installing 2, 3, 4 and 8 baffle-turbulators. According to the results of the study, the average efficiency of a collector with 2, 3, 4 and 8 baffles-turbulators was 29,2%, 31,3%, 33,1 and 33,7%, respectively, in a simple collector – 28,9%.